Gas chromatography–mass spectrometry analysis of various organic extracts of Merremia borneensis from Sabah - M Amzad Hossain; Muhammad Dawood Shah; Mahyar Sakari (Wolters Kluwer Medknow Publications, 2011)
Objective: To analyse the chemical composition of different extracts of Merremia borneensis (M. borneensis) by gas chromatography-mass spectrometry (GC-MS). Methods: The dried leaves powder was extracted with methanol at room temperature by using Soxhlet extractor. Methanol crude extracts of M. borneensis were extrastel with hexane, chloroform, ethyl acetate and butanol. Results: Qualitative analyses of various organic crude extracts showed that majority of these are flavonoids, terpeniods, alkaloids and glycosides. Most of the identified compounds by GC-MS are biologically important. Further the M. borneensis leaf possesses certain characteristics that can be ascribed to cultivation on a domestic plantation. Conclusions: The suitable extracts for respective compounds can be chosen on the basis of above GC-MS analysis. All the major compounds from different extracts are biologically active molecules. Thus the identification of a good number of compounds from various extracts M. borneensis might have some ecological significance.